NEONATAL DIABETES MELLITUS IN 2,5 MONTH OLD CHILDREN - Ivanny Khosasih (HUMAN CARE JOURNAL, 2021)
Neonatal Diabetes mellitus (NDM) is a rare genetic disease (1 in 90,000 live births). It isdefined by the presence of severe hyperglycaemia associated with insufficient or nocirculating insulin, occurring mainly before 6 months of age and rarely between 6 monthsand 1 year. Such hyperglycaemia requires either transient treatment with insulin in abouthalf of cases, or permanent insulin treatment. In transient NDM, growth-retarded infantsdevelop diabetes in the first few weeks of life, only to go into remission after a few monthswith possible relapse to permanent diabetes usually around adolescence or in adulthood. Inpermanent NDM, insulin secretory failure occurs in the late fetal or early postnatal period.We present a case of 9 months old boy with neonatal diabetes mellitus since 2 months 15days old. He had history of fever, polyuria, polydypsia, tachypnoe and diabetic ketoacidosis.He came with hyperglycemia, positive urine ketone and acidosis. C-peptide result was low(0,1 mg/dl). Patient was hospitalized for acute conditions according to DKA managementand continued with insulin subcutaneous. Neonatal diabetes mellitus was a rare condition.The cardinal symptoms of NDM include hyperglycemia at birth, IUGR, failure to thrive,dehydration, and, rarely, ketoacidosis. Treatment with insulin should be started immediatelyafter diabetes is diagnosed by persistent hyperglycemia or elevated glycated hemoglobin(HbA1c). The prognosis is related to the severity of the disease, the degree of dehydrationand acidosis, as well the rapidity with which the disease is recognized and treated. Prognosisalso depends on metabolic control.Keyword: neonatal, hyperglycemia, diabetes mellitus.